Steroidal inhibitor of Na/K‐ATPase marinobufagenin in a mouse model of Alzheimer's disease: Biomarkers (non‐neuroimaging) / Novel biomarkers. (7th December 2020) - Fedorova, Olga V; Zahariadis, Eleni; McDevitt, Ross; Grigorova, Yulia N; Wei, Wen; Zernetkina, Valentina I; Juhasz, Ondrej; Zheng, Lucy; Petrashevskaya, Natalia; Camandola, Simonetta; Mattson, Mark P; Lakatta, Edward G
Abstract: Background: Cardiotonic steroids (CTS), Na/K‐ATPase (NKA) ligands, have potential neuroprotective effects. Despite the importance of the NKA and CTS in the brain physiology, their roles in Alzheimer's disease (AD) pathology are not fully elucidated. Bufadienolide CTS, marinobufagenin (MBG), was lower in 15‐month old double‐mutant Alzheimer's mice (APPswe/PS1dE9; AD) compared to age‐matched wild type (WT) controls. The present study examined whether the treatment with MBG affects behavioral and other parameters in the mouse AD model. Methods: Fifteen‐month old male AD and WT mice were administered MBG (100 µg/day/kg body weight; AD‐MBG, n=8; WT‐MBG, n=4) or vehicle (control: AD‐C, n=8; WT‐C, n=4) using subcutaneous ALZET osmotic minipumps for 3‐month. Systolic blood pressure (SBP; by tail cuff plethysmography), open field test (OFT), home cage activity (HCA), plasma and brain cortex were collected in 18‐mo old mice. SBP was assessed because MBG may increase blood pressure. Statistical analysis: 2‐way ANOVA, t‐test; data presented as mean±SEM. Results: SBP and heart rate did not differ between WT‐C and AD‐C. MBG administration did not affect SBP, and increase heart rate in WT‐MBG vs. WT‐C. Plasma MBG was lower in AD‐C vs. WT‐C and increased in both WT‐MBG and AD‐MBG (Table). No differences were found in HCA, and in OFT for total distance traveled, nor for time spent in the center between AD‐C and WT‐C, and between AD‐C and AD‐MBG. MBG caused a greater reduction in distance traveled in the center for WT mice than it did for AD mice (Table). AD‐C mice had 1.6‐fold higher expression of inflammatory marker interleukin‐6 (IL6) mRNA in cortex vs. WT‐C; MBG treatment reversed this expression in AD‐MBG (Table). Conclusion: AD mice had lower endogenous plasma MBG and higher brain pro‐inflammatory mRNA marker IL6 vs. WT mice. Treatment with MBG significantly reduced levels of this inflammatory marker. WT mice exhibited more exploratory behavior than AD mice in the OFT; MBG decreased exploratory behavior. The additional behavioral tests may be needed to assess the MBG effects on different cognitive components. The association of the brain inflammatory response, cognitive functions and MBG will be further explored in this AD mouse model. Supported by the NIH/NIA Intramural Research Program.